A new belt and road framework method based on the Internet of Things (IoT) for industrial applications - Zhang, Decai; Ali, Mass Hareeza (IJRITCC, 2022)
A network called the Internet of things (IoT) enables data communication amongst all autonomous inanimate devices. It is a network that enables users to practice object communication. Its development marks a significant turning point in digital technologies. The IoT is growing, and with it, the amount of research being done on its foundation. The western region's economic growth should take advantage of this growth and find a path that works for it. There are many flaws and issues in the accounting system of enterprises as a consequence of the development of internal management aspects. In order to aid the west area's quick development, this article is focused on the optimization of the financial growth trajectory of that region against the "Belt and Road" framework. The interaction development route of related industries and modern urbanization is presented in this research. The future total GDP and per capita GDP of the west area are studied and reported using simulated data. According to the data, the west area's total GDP and per capita GDP will expand annually over the following 4 years and afterwards continue to grow.